2022
DOI: 10.1002/anie.202206915
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Interfacial Boron‐Nitrogen Moieties in Turbostratic Carbon for Electrochemical Hydrogen Peroxide Production

Abstract: The electrochemical oxygen reduction reaction (ORR) provides a green route for decentralized H2O2 synthesis, where a structure–selectivity relationship is pivotal for the control of a highly selective and active two‐electron pathway. Here, we report the fabrication of a boron and nitrogen co‐doped turbostratic carbon catalyst with tunable B−N−C configurations (CNB‐ZIL) by the assistance of a zwitterionic liquid (ZIL) for electrochemical hydrogen peroxide production. Combined spectroscopic analysis reveals a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…The electrocatalysts with optimal interfacial B–N moieties exhibited an H 2 O 2 yield of ∼1787 mmol per g catalyst·per h at −1.4 V in a flow-cell reactor under alkaline conditions. 65 For wastewater treatment, the normalized accumulation of H 2 O 2 in the nitrogen-doped cathode was 9.49 ± 0.03 mg L −1 h −1 cm −2 , and the degradation and mineralization rate of sulfathiazole was 98.25 ± 0.14% and 70.57 ± 0.27% after 180 min treatment, respectively. 66…”
Section: Selectivity During the Cathodic Reduction Processmentioning
confidence: 91%
See 1 more Smart Citation
“…The electrocatalysts with optimal interfacial B–N moieties exhibited an H 2 O 2 yield of ∼1787 mmol per g catalyst·per h at −1.4 V in a flow-cell reactor under alkaline conditions. 65 For wastewater treatment, the normalized accumulation of H 2 O 2 in the nitrogen-doped cathode was 9.49 ± 0.03 mg L −1 h −1 cm −2 , and the degradation and mineralization rate of sulfathiazole was 98.25 ± 0.14% and 70.57 ± 0.27% after 180 min treatment, respectively. 66…”
Section: Selectivity During the Cathodic Reduction Processmentioning
confidence: 91%
“…The electrocatalysts with optimal interfacial B-N moieties exhibited an H 2 O 2 yield of ∼1787 mmol per g catalyst$per h at −1.4 V in a ow-cell reactor under alkaline conditions. 65 For wastewater treatment, the normalized accumulation of H 2 O 2 in the nitrogen-doped cathode was 9.49 ± 0.03 mg L −1 h −1 cm −2 , and the degradation and mineralization rate of sulfathiazole was 98.25 ± 0.14% and 70.57 ± 0.27% aer 180 min treatment, respectively. 66 N-doped groups and oxygen-containing functional groups could coexist in the carbon cathodes for the 2e − ORR as the surface pyridine-N improves interface electron transfer, while pyridine-N increases 2e − ORR selectivity, and the surface C]O groups provide strong chemical adsorption for O 2 .…”
Section: Selectivity During the Cathodic Reduction Processmentioning
confidence: 92%
“…Electrocatalytic reactions occur at the electrified electrode‐electrolyte interface. Both the electrocatalysts and electrolytes strongly impact the electrochemical performance [3, 19–26] . However, the underlying regulation mechanism of the electrolyte components in the interfacial environment remains elusive and an important topic in electrochemistry performance [25] …”
Section: Introductionmentioning
confidence: 99%
“…Both the electrocatalysts and electrolytes strongly impact the electrochemical performance. [3,[19][20][21][22][23][24][25][26] However, the underlying regulation mechanism of the electrolyte components in the interfacial environment remains elusive and an important topic in electrochemistry performance. [25] Recent studies have shown that changing electrolyte composition (cations, anions, solvents, additives, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…19 To evaluate the electrocatalytic performance, the potential of the Pt ring electrode was set at 1.2 V (vs RHE) with the potentiostat to oxidize as-formed H 2 O 2 at the disk electrode for measuring the production of H 2 O 2 . 20 The catalyst was cast onto the rotating ring disk electrode (RRDE), with the collection efficiency of the Pt ring in the RRDE determined by the redox reaction of [Fe(CN) 6 ] 4− /[Fe(CN) 6 ] 3− (Figure S11). 21 Figure 3a displays the polarization curves and the oxygen reduction current recorded on the AF-DCN-HMC electrode, with the corresponding HO 2 − oxidation current measured on the Pt ring electrode.…”
mentioning
confidence: 99%